Carbon‐dioxide Removal and Biodiversity: A Threat Identification Framework. (3rd September 2020) - Dooley, Kate; Harrould‐Kolieb, Ellycia; Talberg, Anita
Abstract: Carbon‐dioxide removal (CDR) technologies offer the potential to contribute to the restoration and protection of natural ecosystems, the achievement of development goals and the safeguarding of human wellbeing. However, these technologies can also present risks to biodiversity, particularly those techniques that depend on large‐scale manipulation of ecosystems and earth‐system processes. Debates around the development of these technologies have historically focused on the dichotomy between the need to expand the knowledge base on all options related to emerging technologies, and the concern that research represents a slippery slope to deployment. This paper introduces a new approach to governing CDR research – one based on threat identification. We present a framework for assessing the impacts (positive or negative) on biodiversity and ecosystems from a spectrum of CDR interventions, so as to prioritize research to those CDR options that present minimal threats to biodiversity. Application of the framework indicates that while many CDR interventions present threats to biodiversity, certain options, such as regenerative CDR, may have positive impacts. Abstract : With the exception of removal options that restore and regenerate nature, our analysis suggests that CDR should be viewed as an intervention with likely negative impacts on biodiversity loss, adding to the imperative for rapid and deep decarbonization to minimize any future CDR reliance.